PROPOSAL OF SPECIFIC OPERATIONAL MEASURES SUPPORTING RAILWAY PASSENGER TRANSPORT DURING THE PANDEMIC (Perner's Contacts, 2023)
The unexpected development of COVID-19 has had a significant impact on the traveller's habits. Even before the pandemic, public passenger transport performance had already a decline trend and a high increase was recorded in individual car transport. The emergence of COVID-19 has significantly reinforced this negative trend and public passenger transport has become the preferred choice of travellers. This paper deals with the impact of measures introduced in the first half of 2020 on passenger rail transport in the Slovak Republic in order to slow down the spread of the virus during the first wave of the COVID-19 pandemic. The main objective of the paper is to investigate and to analyse the decrease in transport performance in individual months of the first half of 2020 and then to estimate the impact of these changes on the passenger rail sector. The transport performance is then analysed on three important railway lines in the Slovak Republic, comparing the years 2018, 2019 and 2020. In general, it is expected that a certain period after the end of the pandemic situation may be critical to ensure long-term and sustainable development within the rail transport sector.
Keywords: measures; COVID-19 pandemic; transport performance